Pandangan Al-Ghazali tentang Qadim dan Baharu Alam Semesta - Suma Hayani; Andi Saputra; Saidul Amin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
Mankind needs to study the creation of the universe because it will deliver them the proof, existence and omnipotence of Allah. Allah created the universe as a sign of His love for mankind. He created the universe for the benefit of mankind so that they could easily understand and learn everything in the world. Throughout history, many Muslim philosophers have explained the creation of the universe on their own respective views. One of them is Al-Ghazali through his works of Tahafut Al-Falasifah, Al-Munqidh min Al-Dhalal, Ihya Ulumiddin and Al-Hikmah fi Makhluqatillah. Al-Ghazali systematically formulated the universe based on the Qur'an and Hadith. He mastered various disciplines such as Islamic theology, philosophy and Sufi. He is also known as the consolidator of these three sciences. This is what makes Al-Ghazali a highly acclaimed figure. His acclaimed figure encouraged the author to discuss his concept of qadim and baharu of the universe and the critics of these concepts by other Muslim philosophers. The method used in this research is the literature review with primary and secondary data. These data were classified and analysed carefully before concluded to get the answers to problems. The results show that according to Al-Ghazali, the world must not be qadim. This means that Allah always exists, whereas the world has not. Allah then created the world and the world exists alongside Allah. In other words, Allah, as the creator, is qadim, while the world as the creature is baharu. Allah and the world are very different from their function and position yet some Muslim philosophers claim that Allah and the world are the same, both of which are qadim